Risk Factors, Clinical Features, Health Seeking Behaviour and Treatment for Depression - Rukundo, Godfrey Zari (Research square, 2016)
Depression is a major health problem worldwide [1-3] but commonly unrecognised and untreated. It is one of the most debilitating illnesses in the world and is projected to be the second most common disease by 2020. Depression impairs normal functioning, causes distress and has an adverse effect on an individual’s quality of life. It can cause severe morbidity and has a high incidence of mortality. Depression affects people of different ages and backgrounds. It presents in several ways. The presentation, treatment and complications of depression depend on the severity of the disease. The point prevalence of major depression ranges from 5% to 15% among adults in primary care settings
Keywords: Depression; Illnesses; Morbidity; Risk Factors; Clinical Features